FORMAÇÃO CONTINUADA E ENSINO E LÍNGUA MATERNA SOB A ÓTICA DO LETRAMENTO: A CONSTRUÇÃO DE SABERES MEDIADA PELA UNIVERSIDADE - Macagnan, Maria J. P.; Carnin, Anderson; Urnau, Vanessa E.; Petri, Verlei I. (Salão do Conhecimento, 2013)
Resumo